2001
DOI: 10.1111/j.1748-5827.2001.tb02501.x
|View full text |Cite
|
Sign up to set email alerts
|

Multilobular tumour of bone with no abnormalities on plain radiography in a dog

Abstract: A seven-year-old neutered female golden retriever was presented for an acute onset of cervical pain and ataxia. Intervertebral disc disease or neoplasia was suspected. There was no evidence of a soft tissue or bony mass on physical examination or survey radiographs. Cerebrospinal fluid analysis did not show any evidence of a neoplastic process. Myelographic evaluation identified an extradural mass lesion extending from inside the calvarium to the mid-body of the first cervical vertebra. No additional diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
(1 reference statement)
1
12
0
3
Order By: Relevance
“…Radiation therapy was initiated within 1 week following CT planning using external beam three‐dimensional conformal radiation therapy delivered with 6 MV photons from a linear accelerator (Siemens Primus Mid‐Energy 6 MV linear accelerator, Siemens Medical Systems, Oncology Care Systems Group, Concord, CA). An individualized treatment plan was generated with a computer‐based treatment planning system (Pinnacle 3D Radiation Treatment Planning System, Phillips Medical System N.A., Bothell, WA) using heterogeneity correction. As radiation therapy was performed postoperatively in the microscopic disease setting, there was no gross tumor volume.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Radiation therapy was initiated within 1 week following CT planning using external beam three‐dimensional conformal radiation therapy delivered with 6 MV photons from a linear accelerator (Siemens Primus Mid‐Energy 6 MV linear accelerator, Siemens Medical Systems, Oncology Care Systems Group, Concord, CA). An individualized treatment plan was generated with a computer‐based treatment planning system (Pinnacle 3D Radiation Treatment Planning System, Phillips Medical System N.A., Bothell, WA) using heterogeneity correction. As radiation therapy was performed postoperatively in the microscopic disease setting, there was no gross tumor volume.…”
Section: Resultsmentioning
confidence: 99%
“…Signalment of affected dogs varies with a possible prevalence for middle aged to older, medium to large breed dogs . Dogs most commonly present with a firm, adhered mass of the skull and, depending on the location and extent, can cause obvious deformation of the bone or neurologic deficits . The risk of distant metastasis is relatively unclear, although some studies have suggested a positive association with grade …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations